CARBON REDUCTION AS CARE FOR OUR COMMON HOME: LAUDATO SÍ, CATHOLIC SOCIAL TEACHING, AND THE COMMON GOOD Cristina Richie Boston College - Cristina Richie (Asian Horizons, 2015)
The environmental crisis is a concern for all people and must be addressed effectively and creatively to ensure a reversal of climate change. Now, particularly with the addition of Laudato Sí into the corpus of Catholic Social Teaching (CST), there is reason to include ecology in the conceptualization of the common good. In this article I will analyze three Catholic writings that discuss the idea of the common good from an environmental perspective. I will profile the United States Conference of Catholic Bishop’s Climate Change: A Plea for Dialogue, Prudence, and the Common Good (2001), Benedict XVI’s World Day of Peace Message: If You Want to Cultivate Peace, Protect Creation (2010) and the ground breaking encyclical of Pope Francis, Laudato Sí: On Care for Our Common Home (2015), arguing that Church teachings on the common good include the environment. I will identify carbon reduction as a primary way to care for the common good. Policies that reduce carbon emissions can be enacted through subsidiarity and differentiated responsibilities, both of which are emphasized in CST. Iwill conclude by reiterating that the environment is part of the common good in Catholic Social Teaching, most recently expressed in Laudato Sí.